2015
DOI: 10.1016/j.ypmed.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family history assessment on communication with family members and health care providers: A report from the Family Healthware™ Impact Trial (FHITr)

Abstract: Objective This study examines the impact of Family Healthware™ on communication behaviors; specifically, communication with family members and health care providers about family health history. Methods A total of 3786 participants were enrolled in the Family Healthware™ Impact Trial (FHITr) in the United States from 2005-7. The trial employed a two-arm cluster-randomized design, with primary care practices serving as the unit of randomization. Using generalized estimating equations (GEE), analyses focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Communication outcomes following the use of a tool like VICKY are being examined in the parent trial. VICKY, as with other family history tools, can serve as a trigger to get individuals to think about their health and motivate them to engage in conversations with family members and health care providers to learn more information [48]. Future research efforts should focus on identifying where to disseminate and how best to implement family health history tools like VICKY to ensure broader reach and impact.…”
Section: Discussionmentioning
confidence: 99%
“…Communication outcomes following the use of a tool like VICKY are being examined in the parent trial. VICKY, as with other family history tools, can serve as a trigger to get individuals to think about their health and motivate them to engage in conversations with family members and health care providers to learn more information [48]. Future research efforts should focus on identifying where to disseminate and how best to implement family health history tools like VICKY to ensure broader reach and impact.…”
Section: Discussionmentioning
confidence: 99%
“…Although FHH information has been underutilized in medicine (Berg et al, 2009), research has shown that provision of FHH information is associated with improved health behaviors including physical activity (Ruffin et al, 2011), nutritional intake (Pijl et al, 2009; Ruffin et al, 2011), and cancer screening (Hailey, Carter, & Burnett, 2000). Wang et al (2015) further provided insight into how provision of FHH-based risk information may lead to health behavior change. They found that receipt of tailored FHH-based risk increased communication about and active collection of familial disease risk.…”
Section: Family Health History Information For Family-based Interventmentioning
confidence: 99%
“…To date, multiple tools (e.g., Family Healthware™, Yoon et al, 2009; Rubinstein et al, 2011; U.S. Surgeon General’s My Family Health Portrait; https://familyhistory.hhs.gov) have been made available to families and healthcare providers to facilitate these discussions and for use as a potential screen for cancer risk (Yoon et al 2002; Wang et al, 2015). However, despite wide recognition of family health history as relevant for one’s health many Americans remain unaware that they may be at increased disease risk based on their family history alone potentially because this information is not being communicated within families.…”
Section: Introductionmentioning
confidence: 99%